2012
DOI: 10.1080/15421406.2012.701108
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally-Narrowed Emissions from Organic Transistors Composed of Layered Crystals Laminated on a Two-Dimensional Diffraction Grating (Spectral Narrowing from Organic Crystal Transistors)

Abstract: We observed current-injected spectrally narrowed emissions (SNEs) from a lightemitting field-effect transistor (LEFET) characterized by both layered organic semiconductor crystals and a two-dimensional (2D) diffraction grating. The grating fabricated using nanoimprint lithography had circular air holes forming a triangular lattice. We laminated the p-and n-type crystals in this order on the grating and deposited heterogeneous metal drain and source electrodes. The several SNE peaks were definitively observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(17 reference statements)
0
7
0
1
Order By: Relevance
“…Resonator structures such as distributed feedback (DFB) cavity 6 , single crystal based F-P cavity 7 as well as grating cavity 8 have been investigated in OLEFETs, however, the linewidth (full width at half maximum, FWHM) was limited in the range of 10~25 nm. There were some other reports on 1D/2D photonic crystal imported in OLEFETs which resulted in very narrow linewidth, however, the fabrication process of photonic crystals, such as electron-beam lithography, reactive ion etching and lamination, would probably bring some physical damage to the morphology of OLEFETs, leading to poor device performance 9 10 . Considering that the emission from OLEFETs is mainly in the vertical direction, it would be more appropriate to introduce a resonator vertically.…”
mentioning
confidence: 99%
“…Resonator structures such as distributed feedback (DFB) cavity 6 , single crystal based F-P cavity 7 as well as grating cavity 8 have been investigated in OLEFETs, however, the linewidth (full width at half maximum, FWHM) was limited in the range of 10~25 nm. There were some other reports on 1D/2D photonic crystal imported in OLEFETs which resulted in very narrow linewidth, however, the fabrication process of photonic crystals, such as electron-beam lithography, reactive ion etching and lamination, would probably bring some physical damage to the morphology of OLEFETs, leading to poor device performance 9 10 . Considering that the emission from OLEFETs is mainly in the vertical direction, it would be more appropriate to introduce a resonator vertically.…”
mentioning
confidence: 99%
“…Clear mode selections at the intended wavelengths were obtained and the laser threshold was reduced signicantly. [81][82][83][84] Nevertheless, the applications directly onto ambipolar LET were still not optimum, since the electronic transport properties of the transistors were compromised. Recently, Fang, et al demonstrated direct patterning of the TPCO single crystal, BP2T, to become a DFB structure by means of the laser interference ablation method 85 that exhibit lasing with a FWHM as small as 1.5 nm and threshold energy of 25 mJ cm À2 .…”
Section: Resonator Structuresmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] These cavities and resonators are often used for optoelectronic devices such as light-emitting field-effect transistors (LEFETs). [18][19][20][21][22][23] The aforementioned optical cavities can be fabricated through nanopatterning, e.g., focused ion beam (FIB) 14,19) and interference exposure. 20) The nanopatterning can be carried out by embossing a plastic film using micro-/nanomold and nanoimprint methods.…”
Section: Introductionmentioning
confidence: 99%